Physiotherapy and Physical Activity as Factors Improving the Psychological State of Patients With Cancer - Zyzniewska-Banaszak, Ewelina; Kucharska-Mazur, Jolanta; Mazur, Aleksandra (Frontiers in Psychiatry, 2021)
Physiotherapy in oncology is a process closely related to cancer treatment methods. Rehabilitation is based on physical activity in various forms involving the musculoskeletal system but also affects the emotional state. Physical activity influences physical and psychological well-being of people undergoing oncological treatment, in the course of which the most common psychiatric disorders are depression, substance use disorder, sleep disorders, fatigue syndrome, resulting in worsening of the quality of life. Difficulties in implementing physical exercise in cancer patients pose a challenge to treatment teams.